Complete chloroplast genome of Sphagnum subsecundum Nees from Korea - Wonhee Kim; Seah Ryu; Ji-Hee Song; Sunhee Sim (Mitochondrial DNA. Part B. Resources, 2021)
We determined the complete chloroplast genome sequence of the peatmoss Sphagnum subsecundum Nees from Mt. Halla in Korea. The total size of the chloroplast genome was 140,136 bp, and it consisted of a large single-copy region (LSC) of 98,064 bp, a small single-copy region (SSC) of 21,388 bp, and two copies of inverted repeat (IRa and IRb) regions of 10,342 bp each. The genome encoded a set of 130 genes, comprising 85 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. This species formed a monophyletic clade with S. orientale and S. lenese as the result of ML phylogenetic analysis based on whole gemone sequence of 15 species including one outgroup species.